Shear behavior of reinforced concrete beams made from recycled coarse and fine aggregates. (June 2020) - Al Mahmoud, F.; Boissiere, R.; Mercier, C.; Khelil, A.
Abstract: The study of the properties of Recycled Aggregates (RA) and the basic properties of RA concrete has been on going over the last few decades, leading a number of countries to establish standards or recommendations supporting their use. In all the cases, the full and partial replacement of the Natural Aggregates (NA) with recycled alternatives has been proven a feasible option. This study focuses on the effects of small and high replacement ratios of recycled coarse and fine aggregates on shear behavior of reinforced concrete beams. The originality of this work is the investigations of the effect of the addition of recycled fines on the structural properties of recycled concretes. Both materials were compared with conventional concrete as a reference. All the beams are tested statically in four-point loading up to failure. The failure modes, the cracking behavior and the mechanical performance of all beams were studied. The experimental results were compared with the shear provisions of selected standards.